Pulse regime and vegetation communities in fluvial systems: The case of the Parana River floodplain, Argentina - Marchetti, Zuleica Yael (2012)
Aim of this study was to evaluate the influence of flood pulse regime attributes (pulse frequency, pulse average intensity and amplitude, and flooded days) on the floristic differentiation of the Argentinian Middle Parana river floodplain vegetation in a 39-year period. Besides on floristic composition richness, diversity, evenness, percentage of woody species and topographic position were assessed for 7 communities. Pulse regime attributes were evaluated for each community taking into account different topographic positions and hydrological levels of the Parana River. Our result showed that fluvial vegetation is not floristically differentiated according to its topographic position and there is a weak relation between pulse regime attributes and diversity of woody and herbaceous species. Because of the same topographic position has been colonized by different vegetation communities, floristically different communities share similar pulse frequency, pulse average intensity and amplitude, and flooded days. Pulse regime effects on fluvial vegetation are dependent on more than the topographic position; other aspects of the dynamics of fluvial systems such as the geomorphologic architecture, sediment load and channel dynamics should be included in order to explain the floristic differentiation of the Parana River floodplain vegetation.